From single to scale : how a single person, small business, or an entrepreneur can grow their business to profit - Killen, Michael (Apress, 2019)
Scale your single-person business to profitability. Increase your audience, create multiple products, and generate more profit. This book takes you through the entire process of building a scalable business from the seemingly impossible place of "being just one person." Most single-person businesses are stuck in a pattern of exchanging time for money. Through this book, you will learn how to beat that feast or famine cycle of work. Ask yourself the following questions: Do I have to do the work or can I outsource it to someone else? Can I receive 1,000 orders tomorrow and handle it? Is the process/delivery repeatable so anyone can do it? What You'll Learn: Develop a profitable, scalable business from what you're doing now Create content and attract an audience to that content Outsource your scalable process Scale your profit and money management Optimize your growth and prioritize meeting and exceeding your goals